2012
DOI: 10.1073/pnas.1203799109
|View full text |Cite
|
Sign up to set email alerts
|

3′ Phosphatase activity toward phosphatidylinositol 3,4-bisphosphate [PI(3,4)P 2 ] by voltage-sensing phosphatase (VSP)

Abstract: Voltage-sensing phosphatases (VSPs) consist of a voltage-sensor domain and a cytoplasmic region with remarkable sequence similarity to phosphatase and tensin homolog deleted on chromosome 10 (PTEN), a tumor suppressor phosphatase. VSPs dephosphorylate the 5′ position of the inositol ring of both phosphatidylinositol 3,4,5-trisphosphate [PI(3,4,5)P 3 ] and phosphatidylinositol 4,5-bisphosphate [PI (4,5)P 2 ] upon voltage depolarization. However, it is unclear whether VSPs also have 3′ phosphatase activity. To g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
82
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(95 citation statements)
references
References 34 publications
12
82
1
Order By: Relevance
“…Moreover, in line with our conclusion, previous functional assays in living cells did not support a role in 3-phosphoinositide signaling ( 11 ), and recent in vitro data are fully consistent with the 5-phosphatase activity ( 25 ). The apparently different enzymatic specifi city previously observed in vitro might therefore point to the importance of the native membrane environment in determining the stereochemistry of interaction of the phosphatase with its phospholipid substrate.…”
Section: Enzymatic Properties Of Mammalian Vspssupporting
confidence: 79%
See 2 more Smart Citations
“…Moreover, in line with our conclusion, previous functional assays in living cells did not support a role in 3-phosphoinositide signaling ( 11 ), and recent in vitro data are fully consistent with the 5-phosphatase activity ( 25 ). The apparently different enzymatic specifi city previously observed in vitro might therefore point to the importance of the native membrane environment in determining the stereochemistry of interaction of the phosphatase with its phospholipid substrate.…”
Section: Enzymatic Properties Of Mammalian Vspssupporting
confidence: 79%
“…overexpressed Ci-VSP induced a dissociation of the PI(3,4)P 2 probe TAPP1-PH from the membrane at strongly depolarized potentials ( 25 ). We have not observed such apparent depletion of PI(3,4)P 2 by Ci-VSP in mammalian cells previously ( 2 ).…”
Section: Enzymatic Properties Of Mammalian Vspsmentioning
confidence: 59%
See 1 more Smart Citation
“…Subsequently, VSPs were reported to cleave 3-phosphate from PI(3,4)P 2 , generating PI(4)P upon larger depolarization (20), and, very recently, Ci-VSP was indicated to cleave 3-phosphate from PI(3,4,5)P 3 , generating PI(4,5)P 2 (21,22). Because different substrate reactions are best seen at different voltages, several authors have suggested that changing electric fields can drive VSPs successively through several catalytically active states that favor one set of substrates or reactions over another (20)(21)(22). The active site of VSPs is well conserved among species (12) and shows only a single amino acid difference from the active site of PTEN (1).…”
mentioning
confidence: 99%
“…Upon depolarization VSPs dephosphorylate the 5 position of PtdIns(3,4,5)P 3 and PtdIns(4,5)P 2 and the 3 position of PtdIns(3,4)P 2 (Kurokawa et al, 2012). In the present conditions, we tend to favor PtdIns(4,5)P 2 as the active molecule because of its rich history of function in regulating ion channels and transporters in the plasma membrane of various cell types, and also because of our results with the PtdIns(4,5)P 2 -selective PLC 1 PH probe.…”
Section: Discussionmentioning
confidence: 99%